2019
DOI: 10.1111/lnc3.12310
|View full text |Cite
|
Sign up to set email alerts
|

The life and times of focus alternatives: Tracing the activation of alternatives to a focused constituent in language comprehension

Abstract: The function of focus is to activate a set of alternatives, providing the locus for focus‐sensitive particles like only. In the past decade, psycholinguistic research has shown that listeners entertain a set of alternatives in online language comprehension, similar to the algorithm stipulated by Alternative Semantics. The purpose of the present review is to gain a comprehensive picture of the role of focus alternatives in utterance comprehension and interpretation. Specifically, we focus on how the processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…Thus, we cannot claim that our results generalise over linear position and syntactic and thematic roles. However, some previous findings suggest that such a generalisation is possible: Gotzner and Spalek (2019) showed that, after a certain amount of time, alternatives (compared to non-alternatives) remain active for a long time period after listening to a focused element. This alleviates concerns about the linear position of focus, with subject focus (in Rel_NoAlt) always occurring earlier than object focus (in Rel_Alt).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we cannot claim that our results generalise over linear position and syntactic and thematic roles. However, some previous findings suggest that such a generalisation is possible: Gotzner and Spalek (2019) showed that, after a certain amount of time, alternatives (compared to non-alternatives) remain active for a long time period after listening to a focused element. This alleviates concerns about the linear position of focus, with subject focus (in Rel_NoAlt) always occurring earlier than object focus (in Rel_Alt).…”
Section: Discussionmentioning
confidence: 99%
“…Broad evidence suggests that, in language comprehension, contrastive pitch accenting directs listeners' attention to a contrast between the current referent and a previously mentioned referent, whereas presentational pitch accenting directs listeners' attention to new referents more generally (for a review, see Gotzner & Spalek, 2019). For instance, offline memory for referents with contrastive accenting is superior to memory for referents with presentational accenting, particularly when a salient contrasting referent must be rejected (Fraundorf et al, 2010(Fraundorf et al, , 2012Lee & Snedeker, 2016;Sanford et al, 2006).…”
Section: Pitch Accent Interpretationmentioning
confidence: 99%
“…One way in which such entities may be related is via contrast, which refers to a contradiction between relevant features (e.g., The meeting isn't on Friday; it's on Monday; Myhill & Xing, 1996). Although contrast can be discerned semantically after the fact based on salient contradictions between entities (Gotzner & Spalek, 2019), it can also be anticipated based on potentially diagnostic features within the communicative environment, which we term cues (e.g., font, speech, gestural emphasis). Cues facilitate discourse comprehension and strengthen mental representations of propositional relations between contrasting entities insofar as they convey contrast reliably (Fraundorf et al, 2013;Fraundorf et al, 2010Fraundorf et al, , 2012Lee & Snedeker, 2016;Sanford et al, 2006).…”
mentioning
confidence: 99%
“…Turning to focus, Gotzner and Spalek (2019) in a recent review compare the time course of processing for utterances with a prosodically marked focus vs. utterances where in addition a focus particle associates with the focus. The authors report findings supporting the assumption that mere prosodic focus marking causes an immediate activation of all sorts of related concepts, not just focus alternatives (contrastive alternatives in the section Focus and Contrastive Topics).…”
Section: The Time Course Of the Activation Of Alternatives During Processingmentioning
confidence: 99%
“…This decision was made more slowly in sentences with a focus particle than in sentences without a particle. Gotzner and Spalek (2019) assume that the presence of a focus particle triggers an active search for relevant alternatives and that this search causes activated elements to compete, which leads to interference during processing. Eventually though, as in the case for prosodic prominence, focus particles improve memory for alternatives (Spalek et al, 2014).…”
Section: The Time Course Of the Activation Of Alternatives During Processingmentioning
confidence: 99%